Electronic Medical Community: What Rules, What Specifications? - V, Mishlanov; A, Chuchalin; V, Chereshnev; V, Poberezhets; K, Kostikas; A, Zuev (Archives of Clinical and Biomedical Research, 2021)
The aim of the review is to summarize our knowledge in digital medicine today and present a structural scheme with different perspectives for its development. The electronic medical community is forming spontaneously due to technological progress, the present epidemiological status of the community and tendency for electronic cooperation. The clinical review includes methodology, the relevance of telemedicine development during the Covid-19 pandemic era, an overview of the instruments for remote home-based medicine, the presentation of new methods for remote preliminary diagnostics making. It also considers the role of artificial intelligence achievements in the field of remote medical monitoring, the discussion on randomized clinical trials needs in telemedicine and personal data protection as a biomedical problem.